A mechanistic analysis of the influence of iron‐oxidizing bacteria on antimony (V) removal from water by microscale zero‐valent iron. Issue 9 (25th March 2018) - Li, Yongchao; Wu, Jixin; Hu, Wei; Ren, Bozhi; Hursthouse, Andrew S
Abstract: BACKGROUND: Microscale zero‐valent iron (mZVI) is an efficient material for removing heavy metals from water, and iron‐oxidizing bacteria are the primary microorganisms responsible for iron corrosion. We investigated the effects of Sphaerotilus natans on antimony [Sb(V)] removal by mZVI using batch experiments. RESULTS: At an initial Fe 0 dose of 0.1 g L –1, 40 mg L –1 Sb(V) was almost completely removed in an abiotic system. Although S. natans exhibited significant tolerance to Sb(V), its ability to adsorb Sb(V) was poor. Most importantly, the presence of S. natans reduced the removal rate of aqueous Sb(V) by mZVI by up to 39%. The value of the redox potential in the biologically mediated system was lower than that in the abiotic control, indicating oxygen consumption by S. natans . In the presence of S. natans, the main reaction products were FeOOH and FeSb2 O6, compared to Fe2 O3 in the abiotic system. Biomineralization of Fe 3+ ions by S. natans may have occurred during the experiment, but it did not play a significant role in Sb(V) removal. CONCLUSION: mZVI can be efficiently used to remove Sb(V) from water. However, the presence of S. natans may inhibit its removal ability, likely due to the decreased mass transfer and lower corrosion of iron. © 2018 Society of Chemical Industry